Audit of thromboprophylaxis decision-making at three independent hospice inpatient units. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Powell, Amanda; McMunnigal, Fiona; Dymond, Emma
Abstract : Introduction: Palliative care patients should be considered for thromboprophylaxis, given they are often at risk of thromboembolic events. However many have significant contraindications and therefore decisions require careful consideration of risk/benefit burden. Aim: To identify how medical staff consider and document decisions regarding thromboprophylaxis in patients admitted to three inpatient units (IPU). Methodology: Initial retrospective review of medical case notes, examining entries within 48 h of admission. 100 case notes (30–40 from each hospice) were reviewed for patients admitted to IPUs from 01 May 2010. The second cycle prospectively reviewed 150 case notes (50 from each hospice) after implementation of thromboprophylaxis education, guidelines and alteration of admission notes to incorporate a thromboprophylaxis prompt. Results: Documentation of thromboprophylaxis improved from 15% in cycle 1 to 93% in cycle 2. Nine (53%) and 26 (68%) patients already on anticoagulant treatment, remained on treatment, in cycles 1 and 2 respectively. Eighty-three patients (83%) in cycle 1 were not on anticoagulation treatment compared to 112 patients (75%) in cycle 2. Thromboprophylaxis was initiated in 0% and 11% of these patients in cycles 1 and 2 respectively. In cycle 2, 96 patients did not receive thromboprophylaxis. Reasons were documented in 88 patients. Fourteen patients had more than one reason. Documented reasons were: 29% no indication or not wished, 27% approaching end of life, 17% gastrointestinal bleeding, 8% anaemia, 6% on medication with additional bleeding risk, 5% bleeding other than gastrointestinal, 4% coagulation defects, 2% cerebral bleeding risk and 2% injection site problems. Discussion: It was clear from cycle 1 that documentation of thromboprophylaxis decisions was poor. Although decisions may have been contemplated, the process was not documented. Education, guidelines and changes to admission notes led to significant improvements in the documentation and transparency of decisions regarding the therapeutic dilemma of thromboprophylaxis in hospice inpatients.